giải pt: `(x+1)/65 + (x+3)/65=(x+5)/61 + (x+7)/59`

giải pt:
`(x+1)/65 + (x+3)/65=(x+5)/61 + (x+7)/59`

2 bình luận về “giải pt: `(x+1)/65 + (x+3)/65=(x+5)/61 + (x+7)/59`”

  1. Giải đáp:
     x= -66
    Lời giải và giải thích chi tiết:
      $\frac{x+1}{65}$ +$\frac{x+3}{63}$ =$\frac{x+5}{61}$ +$\frac{x+7}{59}$
    <=>($\frac{x+1}{65}$ +1 ) ($\frac{x+3}{63}$ +1) = ($\frac{x+5}{61}$ +1) ($\frac{x+7}{59}$ +1 )
    <=>($\frac{x+66}{65}$ ) + ($\frac{x+66}{63}$ )= ($\frac{x+66}{61}$ ) ($\frac{x+66}{59}$ )
    <=> ( x+66) . ( $\frac{1}{65}$ +$\frac{1}{63}$ – $\frac{1}{61}$ – $\frac{1}{59}$ )= 0
    <=> x+ 66=0 ( vì ( $\frac{1}{65}$ +$\frac{1}{63}$ – $\frac{1}{61}$ – $\frac{1}{59}$ ) $\neq$  0)
    <=>  x=-66
    Vậy phương trình trên có tập nghiệm S={ -66}
    #Ng_LinPhuong

    Trả lời

Viết một bình luận

Câu hỏi mới